2010
DOI: 10.1111/j.1365-2621.2010.02463.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein, amino acid, ash and mineral contents in Brassica spp. grown in Northwest Spain

Abstract: The protein, amino acid, ash, and mineral composition of different Brassica spp. grown in several areas of Galicia (Northwest Spain) were studied. The highest protein values were observed in Galega kales (crude protein: 29.66 g per 100 g) and turnip greens and turnip tops (27.74-31.46 g per 100 g), whereas the leaves showed higher protein contents than the stems. Glutamic acid was the most abundant amino acid present (14.53% in turnip greens to 18.45% in white cabbage). Other amino acids such as arginine, aspa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The results showed that the highest content of the 19 amino acids in the 69 varieties of cabbage was Glu, which could reach 12.259 mg/g ( Table 1 ). In the research on Brassica spp., Glu has also been proven to be the most abundant amino acid [ 41 ], which is consistent with the results of our study. An amino acid analysis of 239 apricot varieties showed that the most abundant amino acid is Gly [ 36 ], which is inconsistent with the results of our experiment, but which may be related to the different cultivated species.…”
Section: Resultssupporting
confidence: 93%
“…The results showed that the highest content of the 19 amino acids in the 69 varieties of cabbage was Glu, which could reach 12.259 mg/g ( Table 1 ). In the research on Brassica spp., Glu has also been proven to be the most abundant amino acid [ 41 ], which is consistent with the results of our study. An amino acid analysis of 239 apricot varieties showed that the most abundant amino acid is Gly [ 36 ], which is inconsistent with the results of our experiment, but which may be related to the different cultivated species.…”
Section: Resultssupporting
confidence: 93%
“…Total Ca (mg/g) Bioaccessible Ca (mg/g) The high Ca concentrations reported in the present study are in agreement with those provided in previous works: 19.7 mg/g [29]; 4.3-18.5 mg/g [30]; 6.2-19.5 mg/g [14]. In addition, it has been pointed out that Brassicas are a good dietary source of bioaccessible Ca due to their low content of some chelating agents for Ca such as oxalates [31].…”
Section: Samplesupporting
confidence: 93%
“…The winter-type cultivar is the most cultivated rapeseed in the world, which gives it great economic potential due to the limitation of existing vegetable crops in winter [222]. Green leaves are one of the richest sources of essential minerals, protein, and vitamins [223]; they are rich in antioxidant phenolic compounds and regular consumption of leaves is recommended to prevent the risk of chronic diseases [224][225][226][227][228][229]. Rapeseed leaves are excellent vegetable diets for weight loss, due to their low-fat composition, their richness in calcium (the highest in green leafy vegetables), and their high content of vitamin C [222,230].…”
Section: Vegetable Food Tea and Homeopathymentioning
confidence: 99%